Detection of Aerobic Bacterial Contamination in Frozen Chicken Meat Using the TPC (Total Plate Count) Method: Deteksi Kontaminasi Bakteri Aerob pada Daging Ayam Beku Menggunakan Metode TPC (Total Plate Count) - Mutmainnah, Annisa Alifiya; Suharli, Lili; Kusdianawati; Wijaya, Ardiyanto Chandra (Yayasan Siti Widhatul Faeha, 2025)
This study aims to evaluate the biological quality of frozen chicken meat through pH, early spoilage detection, and total microbial contamination, supporting food safety monitoring. According to SNI No. 01-6366 (2000), the maximum microbial contamination limit (BMCM) for chicken meat is 1 × 10⁴ CFU/g. The study utilized pH tests with litmus paper, the Eber test with Eber reagent, and total plate count (TPC) using the MC-Media Pad ACplus™ method, involving buffer preparation, serial dilution, and colony counting. Results showed all three samples had a normal pH range (5–6), meeting the standard. The Eber test indicated all samples were negative for spoilage, as no NH₄Cl compound was formed. However, TPC results revealed that sample A1 (1 × 10⁴ CFU/ml) met the microbial threshold, while samples A2 (3 × 10⁵ CFU/ml) and A3 (5 × 10⁵ CFU/ml) exceeded the BMCM after 48 hours. The findings suggest that although pH and spoilage indicators were within normal limits, microbial load in some frozen chicken samples surpassed safety thresholds. These results underscore the importance of strict cold chain management and routine microbial testing to ensure food safety and consumer health.